Bond of organizational commitment and work motivation to employee performance at PT BPR Serang Branch - Salsabila, Salsabila; Cahyantise, Seftiana; Rahayu Putri, Ratna Mina Dwi; Haryadi, Didit; Wahyudi, Wahyudi (International Journal of Applied Finance and Business Studies, 2024)
Effective management, thinking about the importance of human resources. Employee performance is an important factor influencing success. In an organization, this is one of the most important functions of a company. This study aims to determine the variables that affect employee performance and develop a theoretical basis for the research model. This study used an associative descriptive quantitative method with 30 respondents drawn into samples using non-probability sampling and saturated sampling / total sampling. Data analysis techniques using linear regression with the help of SPSS software version 26. The results of this study show that the first hypothesis states that employee performance is influenced by organizational commitment; the higher the employee who has organizational commitment, the higher the employee performance. The second hypothesis states that work motivation shows can influence employee performance. The third hypothesis is that employee performance is influenced by organizational commitment and employee work motivation, which can simultaneously accelerate the improvement of employee performance. This research is expected to make theoretical contributions to the literature in this context, certainly in the context of human resource management.